Digital Agriculture: Challenges and Possibilities in India - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
Farmers' incomes in India are very low and efforts have to be made to enhance their incomes. For this, increasing the efficiencies of agricultural production processes and the entire value chain is important. Digital Agriculture is emerging as one of the ways to increase efficiencies and enhance incomes in agriculture globally. We define Digital Agriculture in the Indian context and list the challenges as well as the possibilities for Digital Agriculture in India. We find that lower cost of technology, easy to use portable hardware, pay per use renting models, policy support and harnessing the power of farmer collectives are essential for the success of Digital Agriculture in India.
Keywords: 330